Fecal propionate is a signature of insulin resistance in polycystic ovary syndrome - Sitong Dong; Sitong Dong; Xinrui Yao; Xinrui Yao; Jiao Jiao; Jiao Jiao; Bei Lin; Bei Lin; Bei Lin; Fujie Yan; Xiuxia Wang; Xiuxia Wang; et al. (Frontiers in Cellular and Infection Microbiology)
ObjectiveTo investigate the roles of fecal short-chain fatty acids (SCFAs) in polycystic ovary syndrome (PCOS).MethodsThe levels of SCFAs (acetate, propionate, and butyrate) in 83 patients with PCOS and 63 controls were measured, and their relationships with various metabolic parameters were analyzed. Intestinal microbiome analysis was conducted to identify relevant bacteria. The study took place at the Center for Reproductive Medicine at Shengjing Hospital of China Medical University in Shenyang, from 5 February to 23 May 2023. Logistic regression analyses were used to investigate the relationships between SCFAs, PCOS, and PCOS-related insulin resistance (IR). Differences in bacterial populations between women with PCOS-IR and those with PCOS-non-insulin resistance (NIR) were identified using linear discriminant analysis effect Size (LEfSe). The relationships between bacteria and fecal propionate levels were explored through linear regression analyses. The potential of fecal propionate and microbial profiles as biomarkers for insulin resistance in PCOS patients was assessed using receiver operating characteristic (ROC) curve analysis.ResultsHigher fecal propionate levels were observed in patients with PCOS compared to controls (p = 0.042) and in PCOS-IR compared to PCOS-NIR (p = 0.009). There was no significant difference in fecal propionate levels between the IR and NIR subgroups of women in the control group (p > 0.05). Additionally, higher fecal propionate levels were associated with IR in PCOS (p = 0.039; OR, 1.115; 95% CI, 1.006–1.237). The abundance of Prevotella copri and Megamonas funiformis was higher in PCOS-IR women compared to PCOS-NIR women (LDA score > 3) and correlated with fecal propionate levels (adjusted R² = 0.145, p < 0.001). The area under the curve (AUC) for propionate and the combined presence of P. copri and M. funiformis in predicting PCOS was 78.0%, with a sensitivity of 78.5% and a specificity of 72.4%. Pathways related to carbohydrate metabolism were significantly enriched in the microbiota of the PCOS-IR population but not in the control IR group.ConclusionsHigher fecal propionate levels correlate with PCOS-related insulin resistance. P. copri and M. funiformis might be key functional bacteria. Therefore, the combination of propionate levels and the abundance of these two bacteria may serve as a potential biomarker for insulin resistance in PCOS patients. Regulation of the intestinal microbiome might be beneficial for the metabolic health of women with PCOS.